EDUCATION AS A MODERATOR IN PREDICTING ELECTRICAL/ELECTRONIC WASTE DISPOSAL BEHAVIOUR IN A TYPICAL EMERGING ECONOMY CONTEXT: THE CONCEPTUAL FRAMEWORK (UNIZIK Journal of Marketing, 2025)
This study centers on developing a robust conceptual framework for predicting electrical/electronic waste disposal behaviour in a typical emerging market while using education as a moderator. Although extant literature on pro-environmental behaviour abounds in the mainstream literature, studies that focus on developing conceptual framework on the predictors of waste disposal behaviour among youths in a typical emerging market like Nigeria is scarcely researched and under-reported. It is expedient to develop a robust conceptual framework that is suitable to a typical emerging market with huge informality like Nigeria. The theory of planned behaviour was extended. This study concludes that by incorporating education as a moderator in the relationship between extended variables like environmental knowledge and personal responsibility and key psychological constructs like attitude, subjective norms, and perceived behavioral control, the study offers a thorough understanding of the behavioral aspects supporting e-waste management in a typical emerging economy setting. The study's propositions have several important implications for theory, policy, and practice in the broader discourse on sustainable waste management in poor nations. The addition of education as a moderating variable to the Theory of Planned Behavior (TPB) gives a more comprehensive framework for analyzing e-waste disposal behavior among youths. From a theoretical aspect, the study adds to the richness of TPB by including education as a crucial moderator. Traditional TPB models focus on psychological determinants such as attitudes, subjective norms, and perceived behavioral control, without appropriately accounting for environmental and structural elements.
Keywords: Electrical/Electronic waste, Disposal Behaviour, Emerging Market, Youth, Education.